The radiative characteristics of NH3/N2/O2 non-premixed flame on a 10 kW test furnace. (August 2017) - Murai, Ryuichi; Omori, Ryohei; Kano, Ryuki; Tada, Yuji; Higashino, Hidetaka; Nakatsuka, Noriaki; Hayashi, Jun; Akamatsu, Fumiteru; Iino, Kimio; Yamamoto, Yasuyuki
Abstract: The total radiative heat flux and the radiation spectra under the condition of the ammonia fuel combustion in a 10 kW test furnace were measured to clarify the radiative characteristics in this study. The concentration of oxygen in the oxidizer was varied for the purpose of increasing the flame temperature and radiative heat flux. The results showed that radiative heat flux under the condition of the oxygen enriched (30 vol.%) ammonia non-premixed flame formed in a 10 kW test furnace was more than that of the methane/air non-premixed flame. The peak position of the radiative heat flux measured in case of the ammonia combustion shifted to the downstream region from the burner in comparison with the methane combustion. On the other hand, the oxygen enriched flame shifted back to the upstream side from the burner